Learning experiences of Malay Muslim women breast cancer survivors at a Cancer Resource Center, Malaysia - Mohd Yusoff, Mariana (2015)
The purpose of the study was to understand the learning experiences at a Cancer Resource Center (CRC) from the perspective of Malay Muslim women breast cancer survivors. This study also explored how the context of culture shaped their experiences with the CRC. Previous studies from Western and Malaysia have shown that cancer resource centers played an important role in assisting cancer patients and survivors. However, research on the relevance of information and learning on cancer has been predominantly conducted in the Western countries. This research was guided by the six following research questions: (1) Why breast cancer survivors visit CRC?; (2) What do they learn from CRC?; (3) How do they learn through CRC?; (4) How do they find their experience using CRC: Benefits and Challenges?; (5) What is the ideal CRC?; and (6) How does the context shape their experience with the CRC? A qualitative design using purposive sampling technique was used to collect and analyze the in-depth interview of 10 women breast cancer survivors who fit the inclusion criteria. Each interview was audio taped and lasted approximately 60 minutes. All audio tapes were transcribed verbatim and field notes taken during the interview were added to the transcript. The qualitative analysis employed an ongoing, constant comparative process. The findings indicated that CRC played a vital role in helping people affected by terminal illness such as breast cancer. Informants engaged in learning at CRC for various reasons such as to get more information on cancer, to share knowledge and experiences with others and to socialize. Through CRC they learned on cancer diagnosis, treatment and side effect, food practices and coping strategies. They learned from printed and non-printed education materials, utilizing internet, from peers and the CRC nurses, as well as from the educational activities. From CRC, the informants gained knowledge and information, received psychological support and shared their experiences. However, they faced internal and external challenges that deterred them from learning at CRC. The findings also suggested three major aspects to establish an ideal CRC: (1) the location; (2) the human resource; and (3) the design of CRC. Based on these findings, it was concluded that the establishment of CRC in Malaysia was very beneficial to breast cancer patients and survivors as a place for learning. The findings also revealed that culture influenced the breast cancer survivors learning experience at CRC. The learning was self-directed, non-formal and experiential and collectivist/communal. However, the bigger challenges to expand and sustain the CRC were very much related to minimal support from policy makers as well other administration issues. This study contributed to the growing research in adult education, experiential learning, information need and information seeking behavior especially within the field of Adult Education, Health Education and Health Communication. Furthermore, it also provides evidence that CRC played a significant role as an effective learning platform towards improving the quality of life of breast cancer patients and survivors.